2017
DOI: 10.1186/s12876-017-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of additional surgery after non-curative endoscopic submucosal dissection for early colorectal cancer

Abstract: BackgroundAdditional surgery is recommended when early colorectal cancer (ECRC) is resected by non-curative endoscopic submucosal dissection (ESD) and there is significant risk of lymph node metastasis (LNM). The aim of this study was to investigate the efficacy and safety of additional surgery after non-curative ESD for ECRC and evaluate long-term outcomes.MethodsPatients with ECRC who underwent ESD and additional surgery between July 2007 and November 2013 were identified. Histology and patient data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…At present, only endoscopists with extensive experience in performing en bloc endoscopic resection should perform ESD for lesions with deeper submucosal invasion. The present study did not show significant differences between the two groups in the complication rate (5 vs. 4%, respectively, p = 0.733), which was in line with the findings of previous studies [26].…”
Section: Discussionsupporting
confidence: 93%
“…At present, only endoscopists with extensive experience in performing en bloc endoscopic resection should perform ESD for lesions with deeper submucosal invasion. The present study did not show significant differences between the two groups in the complication rate (5 vs. 4%, respectively, p = 0.733), which was in line with the findings of previous studies [26].…”
Section: Discussionsupporting
confidence: 93%
“…Currently, DSI is the most prevalent criterion to refrain from endoscopic resection or refer for additional surgery. 13,14 However, studies have shown conflicting results on its predictive value, and accumulating evidence suggests DSI is only a weak predictor for LNM in the absence of other risk factors, with rates of approximately 1.6%-2.2%. [15][16][17] This limited risk may outweigh surgery-related mortality and recurrence despite oncologic surgery.…”
mentioning
confidence: 99%
“…ESD is a minimally-invasive treatment that has been widely applied in recent years for the treatment of early-stage CRC; however, both patients and doctors have concerns about the possibility of disease recurrence due to non-curative ESD ( 13 ). Several studies have reported histopathologic and other risk factors for residual cancer and LN metastasis after non-curative endoscopic resection of early-stage CRC ( 7 , 9 , 10 ). Despite the high clinical and practical significance, until now there have been few reports on outcomes from ESD in early-stage CRC ( 14 - 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on non-curative ESD for early CRC mostly focuses on pathological features predicting risk of residual cancer or LN metastasis (7)(8)(9)(10). Very few studies have been found to concentrate on the treatment patterns and outcomes.…”
Section: Introductionmentioning
confidence: 99%